APPLYING THE ECONOMIC ORDER QUANTITY (EOQ) METHOD FOR THE CONTROL AND SUPPLY OF SHEEP FEED RAW MATERIALS IN PT. ELDIRA FAUNA ASAHAN - Sri Kartika Hasibuan; Iqbal Kamil Siregar; Iin Almeina Lubis (Informatika, Universitas Jenderal Soedirman, 2022)
Eldira Fauna Asahan is a company engaged in the sale and fattening of sheep, where the process of making sheep feed raw materials is produced by the company itself, which every day requires a lot of raw materials to be produced by the company. The problems that occur in the company today are related to raw materials, where when ordering raw materials there is often a shortage of raw materials or even excess. Currently the raw material ordering system is still based on experience, this causes difficulties in determining the amount of raw materials that must be ordered/provided so that the order sometimes does not match the needs. Therefore, companies currently need an information system that can assist companies in determining the most economical number of orders in one message by applying the ecomoic order quantity (EOQ) method to the system. Then designed information system control and inventory of raw materials for sheep feed at PT. Eldira Fauna Asahan which is useful for determining the number of orders in one message and ordering again as needed. This system is designed using the PHP programming language, stored in the MYSQL database and the visual modeling method uses UML. The result of this research is that this application can later assist companies in determining the amount of raw material needs, and can assist workers in processing data. In conclusion, this application is useful for companies in making it easier for admins to get fast information in determining ordering raw materials.